The occurrence of eastern Common Gulls Larus canus heinei in the region of Öresund - Bengtsson, Kenneth; Pedersen, Kjeld T (Ornis Svecica, 1998)
The common gull Larus canus occurs in the Western Palaearctic with two subspecies. L .c. canus breeds from Britain to western Russia where it is replaced by the slightly larger and darker L. c. heinei. The zone of contact is probably not distinctive and there is therefore a wide zone where birds with characters of both subspecies and intermediate individuals can be found. We have analysed ringing recoveries of birds ringed during the non-breeding season in southern Sweden and Denmark. We demonstrate that this area is frequently visited by birds which return to breeding grounds well into the geographical range of L. c. heinei. This is further supported by data on morphology showing that birds caught during winter are larger than the locally breeding birds. Observations of colour ringed individuals show that birds with a morphology suggesting heinei mainly occur between November and March, though a few, especially younger birds, have been sighted in the area around Oresund throughout the summer months.